Agricultural Polices To Enhance The Development Of Fruit And Vegetable Subsectors In Uzbekistan - Hasanov, Shavkat (European Scientific Journal, ESJ, 2016)
Uzbekistan’s fertile land is highly suitable for growing fruits and vegetables, making it one of the main producers among the Commonwealth of Independent States (CIS) countries. The location of Uzbekistan also provides a ready access to the growing Central Asian and Russian consumer markets. Since its independence, the country implemented a number of agricultural policies targeted at the development of agricultural sector, comprising institutional and structural reforms. The aim of the study is to review the agricultural sector of Uzbekistan and to identify the major constraints to the development of fruits and vegetables subsectors. In doing this, the objective is to put forward policy recommendations for the development of these sector. Fruit and vegetables supply chain potential of the Samarkand region is the key topic of investigation. The recent reforms have provided opportunities for liberalization in agricultural production, especially for the fruit and vegetable subsectors. Yet, modernization of agriculture per se and of the marketing system in Uzbekistan remain areas requiring continued attention for the overall sectorial development. Based on the analysis, the paper provides policy suggestions for implementation. Specific recommendations are outlined pertaining to the identified key constraints; namely, pertaining to agricultural production and productivity, quality of land resources, irrigation, reforms, R&D, and agricultural marketing.